2020
DOI: 10.3389/fpubh.2020.00481
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Incident Dementia Among Older Cubans

Abstract: Introduction: Little is known about risk factors of dementia in Latin American countries. We aimed to identify socio-demographic, health and lifestyle risk factors of incident dementia in Cuban older adults. Methods: Data were from 1,846 participants in the Cuban cohort of the 10/66 Dementia Research Group. Participants completed questionnaires, health examinations, and cognitive tests at baseline (2003-2006) and 4.5 years later (2007-2010). Associations between risk factors (baseline) and incident dementia (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…Similar association studies also reported from other LMICs (51) and HICs (52). A recent study showed the age-specific effect of stroke on dementia, particularly in the younger age group (38). Stroke is the leading health problem in Indonesia since it occupied the first rank of cause of death in our national basic health research (RISKESDAS) in 2013 and 2018, which is 7 and 10.9%, respectively (53,54).…”
Section: Health Factorssupporting
confidence: 73%
See 1 more Smart Citation
“…Similar association studies also reported from other LMICs (51) and HICs (52). A recent study showed the age-specific effect of stroke on dementia, particularly in the younger age group (38). Stroke is the leading health problem in Indonesia since it occupied the first rank of cause of death in our national basic health research (RISKESDAS) in 2013 and 2018, which is 7 and 10.9%, respectively (53,54).…”
Section: Health Factorssupporting
confidence: 73%
“…High cholesterol in late life can indicate a better nutritional status and better overall health, and therefore, it was associated with less cognitive decline (36,37). Several possible mechanisms may explain the abovementioned phenomena (38). Risk factors may occur across the life span, and they take time to affect health in general and the brain in particular.…”
Section: Age-dependent Risk Factors For Cognitive Decline/dementiamentioning
confidence: 99%
“…Database searches identified 16 324 articles, of which 15 658 were excluded based on title and abstract screening (figure 1). We assessed 666 full-text articles, 58 of which reported a study that fulfilled the inclusion criteria 9 11 12 15 32–85. Overall, studies included 257 983 (range: 67–81 087), 128 261 (range: 300–71 157) and 33 870 (range: 638–20 639) participants for all-cause dementia, Alzheimer’s disease and vascular dementia outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation in this study is that about 35% (N = 475) of the eligible sample were lost to follow-up or were not included in the analysis due to incomplete data, similar to other LMIC cohorts (45). The main reason was mass migration from the city due to consecutive years of frequent flooding between 2012 and 2014.…”
Section: Limitationsmentioning
confidence: 98%